2021
DOI: 10.1038/s41598-021-98770-7
|View full text |Cite
|
Sign up to set email alerts
|

One dollar incentive improves tuberculosis treatment outcomes in programmatic settings in rural Uganda

Abstract: The study aim was to determine the association of a one United States dollar (USD) dollar incentive and tuberculosis (TB) treatment outcomes among people with TB receiving treatment at a rural hospital in Uganda under programmatic settings. We conducted a quasi-experiment in which people with TB were randomised (1:1 ratio) to receive either a one USD incentive at months 0, 2, 5 and 6 (Dollar arm) or routine care (Routine arm). A second control group (Retrospective controls) consisted of participants who had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Additionally, since TB treatment requires a lengthy treatment period, conditional cash transfers were suggested to be more appropriate as a TB treatment adherence intervention (Richterman et al, 2018). This is substantiated by the Ugandan one-dollar incentive, which was solely conditional on patients turning up for their clinic appointments, which as previously stated, resulted in improved treatment outcomes (Baluku et al, 2021). Although past studies have also demonstrated that incentives increase TB successful treatment outcomes, these incentives were often too high to be viable standardised practice in resource-limited, developing countries (Ukwaja et al, 2017, Wingfield et al, 2017, Richterman et al, 2018.…”
Section: Socio-economic Supportmentioning
confidence: 96%
See 4 more Smart Citations
“…Additionally, since TB treatment requires a lengthy treatment period, conditional cash transfers were suggested to be more appropriate as a TB treatment adherence intervention (Richterman et al, 2018). This is substantiated by the Ugandan one-dollar incentive, which was solely conditional on patients turning up for their clinic appointments, which as previously stated, resulted in improved treatment outcomes (Baluku et al, 2021). Although past studies have also demonstrated that incentives increase TB successful treatment outcomes, these incentives were often too high to be viable standardised practice in resource-limited, developing countries (Ukwaja et al, 2017, Wingfield et al, 2017, Richterman et al, 2018.…”
Section: Socio-economic Supportmentioning
confidence: 96%
“…As discussed earlier, socio-economic status has a significant impact on TB treatment adherence; hence, social protection is viewed as an essential component of TB control and eradication in the WHO's End-TB Strategy (Baluku et al, 2021, WHO, 2021. Previous studies conducted in developing countries have shown that social protection policies including cash or resource transfers improve TB treatment outcomes (Richterman et al, 2018, Oliosi et al, 2019.…”
Section: Socio-economic Supportmentioning
confidence: 99%
See 3 more Smart Citations